Intermediate monocytes are increased in enthesitis-related arthritis, a category of juvenile idiopathic arthritis. (28th October 2016) - Gaur, P; Myles, A; Misra, R; Aggarwal, A
Summary: Microarray of peripheral blood (PB) and synovial fluid mononuclear cells (PBMC, SFMC) of patients with juvenile idiopathic arthritis–enthesitis-related arthritis (JIA-ERA) has shown the involvement of monocytes. On the basis of CD14 and CD16 expression, monocytes are classified as classical, intermediate and non-classical. In response to Toll-like receptor (TLR) stimulation, intermediate monocytes produce proinflammatory cytokines and play a role in inflammatory diseases. Therefore, we have studied the microarray profile of monocytes, the frequency of their subsets and cytokine production. Monocyte-specific microarray analysis was performed in six healthy controls' PBMC and six patients' PBMC and SFMC using Illumina chips WG12. Monocyte subsets were assessed in 46 patients with JIA-ERA and 17 healthy controls and 17 disease controls by flow cytometry. Interleukin (IL)−23 and tumour necrosis factor (TNF) levels were measured in culture supernatants of eight controls and seven patients' PBMC/SFMC with/without lipopolysaccharide (LPS) stimulation. Cytokine-producing intermediate monocytes were assessed by flow cytometry. Genes related to antigen presentation, cytokine signalling and TLR pathway were regulated differentially in PB and synovial monocytes of patients with JIA-ERA. Key genes of intermediate monocytes, such as CLEC10A and MARCO, were expressed three- to fourfold more in JIA-ERA. In PB, the frequency of intermediate monocytes was significantly higher in JIA-ERA (4·90% ± 3·5) compared to controls (1·8% ± 1·06; P  < 0·001). Patients' synovial cells also had more intermediate monocytes compared to PB (11·25% ± 11·32, 5·9% ± 4·8; P  = 0.004). Intermediate monocytes are the major producers of IL-23. Thus, intermediate monocytes may play an important role in JIA-ERA, possibly by producing cytokines, and contribute to joint inflammation. Graphical Abstract: